Incommensurate van der Waals epitaxy of nanowire arrays : a case study with ZnO on muscovite mica substrates - Belarre, Francisco J. (2013)
The requirement of lattice matching between a material and its substrate for the growth of defect-free heteroepitaxial crystals can be circumvented with van der Waals epitaxy (vdWE). However, the utilization and characteristics of vdWE in nonlamellar/nonplanar nanoarchitectures are still not very well-documented. Here we establish the characteristics of vdWE in nanoarchitectures using a case study of ZnO nanowire (NW) array on muscovite mica substrate without any buffer/seed layer. With extensive characterizations involving electron microscopy, diffractometry, and the related analyses, we conclude that the NWs grown via vdWE exhibit an incommensurate epitaxy. The incommensurate vdWE allows a nearly complete lattice relaxation at the NW-substrate heterointerface without any defects, thus explaining the unnecessity of lattice matching for well-crystallized epitaxial NWs on muscovite mica. We then determine the polarity of the NW via a direct visualization of Zn–O dumbbells using the annular bright field scanning transmission electron miscroscopy (ABF-STEM) in order to identify which atoms are at the base of the NWs and responsible for the van der Waals interactions. The information from the ABF-STEM is then used to construct the proper atomic arrangement at the heterointerface with a 3D atomic modeling to corroborate the characteristics of the incommensurate vdWE. Our findings suggest that the vdWE might be extended for a wider varieties of compounds and epitaxial nanoarchitectures to serve as a universal epitaxy strategy.